Adenocarcinoma arising in Barrett's oesophagus: evidence for the participation of p53 dysfunction in the dysplasia/carcinoma sequence. Issue 6 (June 1994) - Hardwick, R H; Shepherd, N A; Moorghen, M; Newcomb, P V; Alderson, D
Abstract : Adenocarcinoma arising in Barrett's oesophagus is often preceded by mucosal dysplasia, but little is currently known about the aetiology or natural history of this dysplasia/carcinoma sequence. To investigate the participation of the tumour suppressor gene p53 in this sequence, an immunohistochemical analysis of p53 protein overexpression, which is known to closely correlate with point mutation of the p53 gene, was conducted in 30 patients with Barrett's adenocarcinoma. Adjacent Barrett's mucosa was dysplastic in 21 (70%) patients. Sixteen (53%) tumours overexpressed p53, 10 of which had adjacent dysplastic Barrett's mucosa. In all 10 patients, this dysplastic mucosa also overexpressed p53, predominantly in areas of high grade compared with low grade dysplasia. In contrast, none of the dysplastic mucosa adjacent to 11 tumours lacking p53 overexpression showed detectable values of p53. These results suggest that p53 dysfunction may participate in the progression from dysplasia to carcinoma in some patients with Barrett's oesophagus.